al-Daurah al-Mukatsafah: al-Barnamij al-Badil Li Ta’lim Maharah al-Kalam wa al-Qira’ah Fi al-Ma’had - Akmalia, Frida; Syihabuddin, Syihabuddin; Nurbayan, Yayan (Institut Agama Islam Negeri Curup, 2021)
This paper aims to explore an Intensive Course Program in Arabic learning at one of the Islamic Boarding schools for girls in Indonesia. it is expected that Students in this Intensive Course understand two skills in Arabic, namely speaking and reading skills. Also, it aims to identify the strengths and weaknesses of Intensive Course Program. This study utilized a descriptive qualitative approach with three data collection techniques; observation, interviews, and documentation. It used Miles and Huberman’s technique in analyzing the data. This study showed that: 1) Implementation of Intensive Course Program in Arabic learning at the one of Islamic Boarding Schools for girls in Indonesia aimed to improve language skill including reading and deductive skill including speaking. 2) Pertinent to the strengths and weaknesses of the Intensive Course, the learning system is advantagous to enhance other specific skills, ranging from students’ proficiencies in reading and speaking in Arabic. However, there are also drawbacks. For example, an excellent Arabic environment has not been created due to the lack of students’ awareness of making them accustomed to speaking Arabic.